Determinants of Postnatal Care Utilization of Koshi Province (Patan Prospective Journal, 2025)
Postnatal care (PNC) is a vital component in the protection of the health of both newborns and mothers in the postpartum period, which is a crucial age in nature and perspectives, although the use of PNC leaves much to be desired in most low- and middle-income countries. This study will explore factors associated with PNC uptake as utilized in the Koshi Province in Nepal with the use of 2022 Nepal Demographic and Health Survey (NDHS). Using a sample of 504 women and adopting logistic regression approach, the study examines how socio-demographic profiles like age, birth order, education, religion, caste/ethnic, residence and wealth quintile impact on post-natal care usage in the first 48 hours of the birth. The findings show that wealth status is the greatest predictor with women who are in the middle and high wealth quintile having a significantly high chance of obtaining PNC services as compared to low the poorest quintile. There is also significant association with both caste/ethnicity and religion, with women of Brahmin/Chhetri and non-Hindu caste recording high utilization rates. Unlike literature, education level and rural residence were not significantly associated, meaning that structural and financial limitations are at least as important as level of education of the individual. The results show inequalities because of constant socio economic status and social stratification. The study suggests that conditional cash transfers, transport subsidies, and postnatal service inclusion in national health insurance can improve PNC uptake to indicate economic interventions to be implemented. These initiatives combined with outreach and health policies that are sensitive to cultures are critical in ensuring every woman in Koshi Province can get equitable access to maternal healthcare. The research will play a part in the evidence base of the policy changes in Nepal to decrease the maternal disparities in health.